(untitled) (Journal of Social Sciences Review, 2023)
The basic focus of this study was to find out the impact of motivation towards science on the learning level in secondary classes. Accordingly, the hypothesis “there is no effect of motivation on students’ achievement at the secondary level” was designed. Data from 390 teachers were collected and analyzed to address the designed objective and hypothesis, as the study aimed to investigate the impact of motivation on learning achievement in science subjects among secondary-level students. Motivation was categorized into three levels: Low, Moderate, and High. ANOVA analyses were conducted to compare the effects of different motivation levels on students’ achievement. The results revealed a significant difference in learning achievement based on motivation levels. Post hoc tests showed significant differences between Low and High motivation levels, while Moderate and High levels were not significantly different. These findings suggest that motivation plays a vital role in students’ academic performance, particularly in science subjects.